IDENTIFIKASI ETNOMATEMATIKA PERMAINAN TEKA WATU (BATU LIMA) DI DESA RIHUT KABUPATEN MANGGARAI TIMUR - Herlina Nelti Bo; Ningsih Ningsih; Hilaria Melania Mbagho (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This study aims to describe the mathematical elements contained in the traditional puzzle game of the Rihut Village community. This study uses an ethnographic research type with a qualitative approach. The subjects of this study consisted of 2 informants, namely Community Leaders and Mathematics Teachers. In collecting data, interview and documentation techniques were used. Data were analyzed descriptively and qualitatively. The results of the study show that there are mathematical concepts, especially seen in the tools of the stone puzzle game, the rules of the stone puzzle game, and the stone puzzle player. The mathematical concepts found in the stone puzzle game are the concepts of circles, permutations and mathematical logic. (1). The shape of the stone used to play stone puzzles is a round shape resembling a circle. (2). Puzzle players, judging from the sequence of the puzzle games, players start by drawing lots by doing hompimpa. This is where there is the concept of permutations in the puzzle game to calculate the pattern of the puzzle game sequence. (3). Rules of the puzzle game, the concept contained in the rules of the puzzle game is the concept of mathematical logic seen in the right and wrong of a game. Based on the results of the study, the researchers concluded that there are mathematical concepts in the puzzle game, namely circles, permutations, and other mathematical concepts contained in the puzzle tiles such as addition, and subtraction.